Testing of electrical insulation mats in TS 35/10 kV and analysis of the actual situation - Vujić Jovan; Ilić Božo; Đenić Nebojša (Bakar)
The aim of this paper is to present the principle of testing electrical insulation mats and the results of the tests as well as observed irregularities in their operation in transformer stations 35/10 kV (TS 35/10) in Serbia. In accordance with the progress of technology, more and more automation and computers are being introduced in the management of the operation of TS, and the basic concepts of protection against contact voltage and step voltage of the staff who work and stay in these facilities are neglected. The fact is that these TS are facilities where people are not constantly present, but they still spend a certain amount of time in them and are exposed to various dangers. Electrical insulation mats were tested in several TS and the results were devastating. In addition to non-compliance with work procedures, these facilities often leak, various rodents are present, and unsanitary conditions are at an enviable level. The main problem is that the electrical insulating mats are not adequate for their purpose, they are not properly installed, the lack of proper inspection supervision, as well as the shortcomings in the legal regulations that define this area